A new species of Aspidosperma (Apocynaceae) from the Brazilian Cerrado - Scudeler, Ana Laura [UNESP]; Devides Castello, Ana Carolina [UNESP]; De Souza Pereira, Andreza Stephanie; Koch, Ingrid (Magnolia Press, 2018)
Aspidosperma rizzoanum is a new species of Cerrado from Goias and Tocantins states, Brazil. Here we provide the description and illustration of this new species and, besides that, a comparative table and an identification key to the species occurring in the Cerrado of Goias and Tocatins.
Keywords: Apocynaceae; Aspidospermeae; Central-West region; North region; taxonomy